Estimation Of Laterite Nickel Resources Using The Inverse Distance Weight Method PT Premlog Offshore Indonesia Kolaka Regency, Southeast Sulawesi Province - Ardi, Ardi; Jafar, Nurliah (CV Insight Publisher, 2024)
Laterite nickel deposits are ores produced from the weathering process of ultraalkaline rocks on the earth's surface. The term laterit itself is taken from the Latin word